2016
DOI: 10.1097/ijg.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Software Version of the RTVue Optical Coherence Tomograph for Image Segmentation and Detection of Glaucoma in High Myopia

Abstract: Although GCC segmentation was improved with software version 6.12 compared with the current version in highly myopic eyes, this did not result in a significant change of the average RNFLT and GCC values, and did not significantly improve the software-provided classification for glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…All subjects were examined with an RTVue-100 Fourier-domain OCT instrument (Optovue Inc., Fremont, CA, USA) using the scanning protocol “GCC” (ganglion cell complex). The FD-OCT system imaging was performed as described in previous studies [ 29 ]. Briefly, the macular GCC (mGCC) scanning protocol consisted of a 7 mm × 7 mm area, which measured the retinal thickness from the ILM to the IPL posterior boundary.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were examined with an RTVue-100 Fourier-domain OCT instrument (Optovue Inc., Fremont, CA, USA) using the scanning protocol “GCC” (ganglion cell complex). The FD-OCT system imaging was performed as described in previous studies [ 29 ]. Briefly, the macular GCC (mGCC) scanning protocol consisted of a 7 mm × 7 mm area, which measured the retinal thickness from the ILM to the IPL posterior boundary.…”
Section: Methodsmentioning
confidence: 99%
“…There has been some research on improving the software to increase GCC segmentation; however, this did not significantly improve the softwareprovided classification for glaucoma with high myopia. 20 A previous study showed that the cp-RNFL led to false-positive high detection for glaucoma with high myopia. A more accurate diagnosis for HM-G could be made if a normative database in highly myopic eyes were created.…”
Section: Discussionmentioning
confidence: 99%
“…Recent software updates have reduced GCC segmentation errors in patients with macular degeneration, which should allow these patients to be evaluated for glaucoma with more confidence. 133 , 134 Posterior pole asymmetry analysis (PPAA) combines mapping of the posterior pole retinal thickness with asymmetry analysis between eyes and between hemispheres of each eye. 135 Posterior pole asymmetry analysis, although not presently having a built-in normative database, is highly reproducible and matches circumpapillary RNFL measurements in terms of diagnostic accuracy of early glaucoma.…”
Section: Diagnosis Of Glaucomamentioning
confidence: 99%